Project-Based Learning Using Virtual Group in Implementation of Geography Learning Strategy at Curriculum 2013 - Yagus Wijayanto; Elan Artono Nurdin; Bejo Apriyanto; Fahmi Arif Kurnianto; Fahrudi Ahwan Ikhsan (Pancaran Pendidikan, 2017)
This study aims to test the model of project based learning by using a virtual group on the results of learning geography of high school students. The subjects of this study were students of Class X Senior High School 1 Lumajang even semester of academic year 2016/2017 consisting 2 classes. The X-IIS 1 class is set as the experiment class and the X-IIS 2 class as the control class. This is because students in both classes have the same or equivalent abilities based on middle test scores. This research is a quasi-experiment research with Non-Equivalent Control Group Design design. Instrument assessment of learning outcomes using essay tests. Assessment results data that are then analyzed using test-test with the help of SPSS 16.0 for Windows program.The results of this study indicate that there is a significant effect of project-based learning model using the virtual group to the students' geography learning outcomes. Based on pretest and post test differences shows that the mean score of the experimental class gain score (45,63) is higher than control class (30,02). The result of data analysis using independent sample t test showed that project based learning model obtained probability score (p-level) smaller than 0.05 with sign 0,00. The conclusion in this study that the learning model of project-based learning using the virtual group on the results of learning geography of high school students.